Evaluasi Penggunaan Anti Hipertensi Pada Pasien Ibu Hamil Di Rawat Jalan Poli Kandungan Rumah Sakit Kartini Lebak Periode Januari-Juni 2023: Evaluation Of The Use Of Antihypertensives In Pregnant Women In Outpatient Obstetric Polyclinics Of Kartini Lebak Hospitals For The Period January-June 2023 - Ainun Annisa; Julia Totong; Riasa Barata Nian (UIMA Press, 2025)
Hypertension in pregnancy is defined as an increase in systolic blood pressure ≥140 mmHg and/or diastolic blood pressure ≥90 mmHg according to the criteria of the World Health Organization (WHO) and the American College of Obstetricians and Gynecologists (ACOG). This condition requires appropriate management to prevent complications in both the mother and the fetus. This study aimed to evaluate the appropriateness of antihypertensive drug use among pregnant women receiving outpatient care at the Obstetrics and Gynecology Clinic of RS Kartini Lebak. The study employed a descriptive non-experimental design with a quantitative approach. Data were collected retrospectively from the medical records of pregnant women diagnosed with hypertension who received antihypertensive therapy during the study period. A total of 29 patients who met the inclusion criteria were included in the analysis. The results showed that the majority of patients were aged 24–35 years (58.62%). Based on diagnosis, preeclampsia was the most common condition (41.38%), followed by chronic hypertension (37.93%) and gestational hypertension (20.69%). The most frequently prescribed antihypertensive therapy was nifedipine monotherapy (82.76%), while combination therapy with nifedipine and methyldopa was used in 17.24% of patients. Evaluation of drug use appropriateness demonstrated 97% appropriate indication, 97% appropriate drug selection, and 100% appropriate dosage.